Digital Leadership in the Age of Transformation: A Global Bibliometric Analysis of Research Trends and Knowledge Structures - Indarta, Yose (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study examines the evolution and future trends of digital leadership through a comprehensive bibliometric analysis of research publications from 2015 to 2024. The investigation employs bibliometric analysis and topic modeling techniques on metadata from 265 Scopus-indexed articles across 199 distinct sources, focusing specifically on publications with "digital leadership" in their titles. The results reveal a remarkable annual growth rate of 67.18% in publications, with citation patterns demonstrating increasing scholarly impact and recognition. The analysis identifies three distinct thematic clusters characterizing the field's development: digital transformation and innovation, organizational capabilities and adaptiveness, and human-social factors. Additionally, the study uncovers a significant shift in research focus from purely technical considerations to more integrated approaches that encompass human, social, and ethical dimensions, particularly post-2020. The findings indicate six emerging domains that will likely dominate future digital leadership research: AI-augmented leadership, sustainable digital leadership, metaverse leadership, quantum-ready leadership, cross-cultural digital leadership, and digital ethics and well-being. This evolution suggests a transformation in how digital leadership is conceptualized, moving from a technology-centric approach to a more nuanced understanding that balances technological advancement with human factors, sustainability, and ethical considerations in organizational leadership.